Original paperAutoimmunogenicity during anti-TNF therapy in patients with psoriasis and psoriatic arthritis - Pirowska, Magdalena M.; Goździalska, Anna; Lipko-Godlewska, Sylwia; Obtułowicz, Aleksander; Sułowicz, Joanna; Podolec, Katarzyna; Wojas-Pelc, Anna (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2015)
Introduction: The tumor necrosis factor (TNF-α) was initially described as lymphotoxin or cachectin. The discovery of therapies blocking the action of TNF-α, in 1988, started a new era in the therapy. One of often reported adverse effects related to the use of TNF-α antagonists is induction of the formation of autologous antibodies and antibodies neutralizing anti-TNF drugs. The development of anti-TNF-induced lupus or classical drug-induced lupus is more rarely reported. Aim: To evaluate the presence and the level of anti-nuclear antibodies in patients with psoriasis and psoriatic arthritis and the influence of anti-TNF therapy used on the concentration of antinuclear antibody (ANA). Material and methods: A total of 28 subjects were included in the study. 71.4% of subjects were diagnosed with psoriatic arthritis and 28.6% with plaque psoriasis. Results : Among the patients with plaque psoriasis, the antinuclear antibodies were found in 25% of subjects and in 80% of patients with psoriatic arthritis. After the treatment an increase in the titer or appearance of antibodies was found in 66.7% in the infliximab group, 18.2% in the etanercept group and 54.7% in the adalimumab group. No subjects developed symptoms of drug-induced systemic lupus. Conclusions : Our findings have shown that all anti-TNF therapies induced ANA in psoriatic arthritis and psoriatic patients. Considering a mild course of lupus induced by anti-TNF treatment and, usually intrinsic, resolution of symptoms, the biological therapy still appears as a safe treatment for patients.